Economic sociology and political economy: A programmatic perspective - Jens Beckert; Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2008)
The paper presents some of the ideas underlying the current research program of the Max Planck Institute for the Study of Societies (MPIfG). It begins with a discussion of how the institute's programmatic orientation has evolved since it was founded in 1984. Programmatic change over the years involved (1) recognition of a secular decline in the capacity of the nation-state to organize and guarantee social order, and of the growing significance of self-regulating, 'free' national and international markets for social life; (2) increased attention to issues of meaning and to 'culture' and cultural symbolism, as well as to normative questions; (3) a gradual shift in emphasis from policy to politics; and (4) more explicit recognition of history and of the historicity of the questions posed and the observations analyzed in social science. The second part of the paper argues that Gesellschaftsforschung today is most appropriately conceived as the study of the economy and society of contemporary capitalism. It is suggested that the most promising approach is close cooperation between the scholarly traditions of political economy and economic sociology, with the former standing to benefit from a more explicit micro-foundation in a sociological theory of action and the latter from more systematic consideration of politics and the state. Third, the paper shows how the approach that has evolved at the MPIfG differs from mainstream economic sociology, from the so-called new institutional economics, and from behavioral economics. The paper concludes by enumerating four subject areas that are likely to be of particular importance for research at the MPIfG: (1) the nature of rational-economic action, (2) the constitution of markets, (3) the emergence and change of institutions, and (4) the relationship between capitalism and democracy. – – Dargestellt werden einige der dem gegenwärtigen Forschungsprogramm des MPIfG unterliegenden Überlegungen. Das Papier beginnt mit einer Diskussion der programmatischen Entwicklung des Instituts seit seiner Gründung im Jahre 1984. Seit damals eingetretene Veränderungen bestanden vor allem in (1) zunehmender Anerkennung eines langfristigen Rückgangs der Steuerungsfähigkeit des Nationalstaats, bei gleichzeitig wachsender Bedeutung selbstregulierender, 'freier' nationaler und internationaler Märkte; (2) vermehrter Befassung mit kulturellen Sinndeutungen und Symbolen sowie mit normativen Fragen; (3) einer allmählichen Umorientierung von Policy zu Politics; und (4) expliziterer Einbeziehung von Geschichte und Berücksichtigung der Geschichtlichkeit der Probleme und Beobachtungen, die Gegenstand der Sozialwissenschaften sind. Der zweite Teil des Papiers argumentiert, dass Gesellschaftsforschung heute als Untersuchung von Wirtschaft und Gesellschaft des modernen Kapitalismus betrieben werden sollte. Der vielversprechendste Ansatz dazu besteht in einer engen Zusammenarbeit zwischen politischer Ökonomie und Wirtschaftssoziologie. Dabei können die politische Ökonomie von einer expliziteren Mikro-Fundierung in einer soziologischen Handlungstheorie und die Wirtschaftssoziologie von einer systematischeren Berücksichtigung der Politik und des Staates profitieren. Drittens wird dargelegt, wie sich der am MPIfG verfolgte Ansatz vom Mainstream der Wirtschaftssoziologie, von der sogenannten Neuen Institutionellen Ökonomie sowie von der Forschungsrichtung der Behavioral Economics unterscheidet. Das Papier endet mit einer Beschreibung von vier Forschungsthemen, die für die künftige Arbeit am MPIfG von besonderer Bedeutung sein werden: (1) die Natur rationalen wirtschaftlichen Handelns; (2) die Konstitution von Märkten; (3) Entstehung und Wandel von Institutionen; und (4) das Verhältnis von Kapitalismus und Demokratie.
Keywords: 300; Wirtschaftssoziologie; Wirtschaftswissenschaft; Institutionalismus; Deutschland